2011
DOI: 10.1002/jor.22003
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oral administration of glucosamine or chondroitin sulfate reduces destruction of cartilage and up‐regulation of MMP‐3 mRNA in a model of spontaneous osteoarthritis in Hartley guinea pigs

Abstract: Histological and molecular changes were examined to investigate the effects of long-term administration of glucosamine (GlcN) and chondroitin sulfate (CS) in a model of spontaneous osteoarthritis (OA) in Hartley guinea pigs. Three groups of female 3-week-old Hartley guinea pigs received GlcN, CS, and neither agent, respectively. Five animals in each group were sacrificed at 8, 12, and 18 months of age. At 8 months of age, Hartley guinea pigs had severe degeneration of knee joint cartilage, chondrocyte apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
5
26
0
5
Order By: Relevance
“…Our observation that chondrocyte apoptosis is higher in the medial side and largely localised in the deep zone (DZ) of AC supports other studies of spontaneous OA, both in guinea pigs [23] and some human studies [19], but differs considerably from results of studies where OA was induced. Thus, animal models of surgical/injury-induced OA ( i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our observation that chondrocyte apoptosis is higher in the medial side and largely localised in the deep zone (DZ) of AC supports other studies of spontaneous OA, both in guinea pigs [23] and some human studies [19], but differs considerably from results of studies where OA was induced. Thus, animal models of surgical/injury-induced OA ( i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Chondrocyte death by apoptosis has been reported both in human [13,1720] and in animal models of OA [3,9,2123]. In these studies, chondrocyte apoptosis was detected by caspase-3 expression and TUNEL, and confirmed by electron microscopic examination.…”
Section: Introductionmentioning
confidence: 97%
“…Этот важ-ный механизм действия ХС подтвержден в эксперимен-тальных исследованиях: на модели адъювантного артрита у крыс, ХС достоверно уменьшал тяжесть артрита, пода-вляя продукцию провоспалительных цитокинов, СРБ и фагоцитарную активность [35]. В другой эксперименталь-ной модели остеоартроза назначение глюкозамина и ХС снижало экспрессию мРНК матричной металопероксида-зы (ММП), в частности ММП-3, и уменьшало дегенерацию суставного хряща [36].…”
Section: ключевые слова: дорсалгия спондилоартроз структурно-модифициunclassified
“…The applicant also provided studies in animals on the effect of glucosamine on cartilage formation/degradation (Chen et al, 2010;Meulyzer et al, 2009;Naito et al, 2010;Oegema et al, 2002;Taniguchi et al, 2012). Four studies were provided in animal models of OA, i.e.…”
Section: Mechanistic Studiesmentioning
confidence: 99%